Comparison of endoscopic resection techniques for duodenal neuroendocrine tumors: systematic review - Helcio Pedrosa Brito; Isabela Trindade Torres; Karine Corcione Turke; Artur Adolfo Parada; Jaques Waisberg; Ricardo Vieira Botelho (Endoscopy International Open, 2021)
Background and study aims Regardless of size, duodenal neuroendocrine tumors (dNETs) should be considered potentially malignant. A complete resection without complications is essential to increase safety procedures. The aim of this review was to describe effectiveness and possible complications of endoscopic techniques resection for resectioning dNETs in patients with tumors ≤ 20 mm in diameter. Methods An electronic bibliographic search was conducted using MEDLINE (via PubMed), Embase, Cochrane Central, and Google Scholar virtual databases. The types of intervention were endoscopic mucosal resection alone (EMR) or with cap (EMR-C), with a ligation device (EMR-L), with previous elevation of the tumor (EMR-I) or with endoscopic submucosal dissection (ESD); argon plasm coagulation (APC), and polypectomy. The outcome measures adopted were presence of free margin associated with tumor resection, tumor recurrence, complications (bleeding and perforation), and length of the procedure. Results Ten publications were included with the result of 224 dNET resections. EMR alone and polypectomy resulted in the most significantly compromised margin. The most frequent complication was bleeding (n = 21), followed by perforation (n = 8). Recurrence occurred in 13 cases, the majority of those under EMR or EMR-I. Conclusions EMR-C or EMR-I should be preferred for resectioning of dNETs. Polypectomy should not be indicated for resection of dNETs due to the high occurrence of incomplete resections. EMR alone must be avoided due a higher frequency of compromised margin and recurrent surgery. ESD was associated with no recurrence, however, but an increased occurrence of bleeding and perforation.